Pausing methotrexate prevents impairment of Omicron BA.1 and BA.2 neutralisation after COVID-19 booster vaccination - Robert Biesen; Florian Kurth; Jan Zernicke; Florian Klein; Jens Klotsche; Amanthi Nadira Arumahandi de Silva; Leonie Maria Frommert; Alexander ten Hagen; Elisa Habermann; Lutz Gieselmann; Pinkus Tober-Lau; Fredrik Nils Albach; et al. (RMD Open, 2022)
Objective The level of neutralising capacity against Omicron BA.1 and BA.2 after third COVID-19 vaccination in patients on paused or continuous methotrexate (MTX) therapy is unclear.Methods In this observational cohort study, neutralising serum activity against SARS-CoV-2 wild-type (Wu01) and variant of concern Omicron BA.1 and BA.2 were assessed by pseudovirus neutralisation assay before, 4 and 12 weeks after mRNA booster immunisation in 50 rheumatic patients on MTX, 26 of whom paused the medication. 44 non-immunosuppressed persons (NIP) served as control group.Results While the neutralising serum activity against SARS-CoV-2 Wu01 and Omicron variants increased 67–73 fold in the NIP after booster vaccination, the serum activity in patients receiving MTX increased only 20–23 fold. Patients who continued MTX treatment during vaccination had significantly lower neutralisation against all variants at weeks 4 and 12 compared with patients who paused MTX and the control group, except for BA.2 at week 12. Patients who paused MTX reached comparably high neutralising capacities as NIP, except for Wu01 at week 12. The duration of the MTX pause after—not before—was associated with a significantly higher neutralisation capacity against all three variants, with an optimal duration at 10 days after vaccination.Conclusion Patients pausing MTX after COVID-19 booster showed a similar vaccine response to NIP. Patients who continued MTX demonstrated an impaired response indicating a potentially beneficial second booster vaccination. Our data also suggest that a 1 week MTX break is sufficient if the last administration of MTX occurs 1–3 days before vaccination.